2022
DOI: 10.3390/agriculture12081198
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Digestive Effects of Yucca schidigera Extracts Related to Production and Environment Implications of Ruminant and Non-Ruminant Animals: A Review

Abstract: Plant extracts have been used over time in traditional medicine, mainly for their antimicrobial activity as well as for their medicinal effects. Plant-derived products contain secondary metabolites that prevent pathogenic microbial growth similar to conventional medicines. These secondary metabolites can enhance animal health and production in a more natural or organic manner and may contribute to the reduction in the use of pharmacological drugs in animal feed, which is of great concern for emerging microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Chinese herbal medicine extracts have the advantages of natural sources, no pollution, low cost, etc., and are rich in a variety of active substances and have a wide range of effects, which may have the potential to reduce ammonia gas in laying hens. Yucca extract has been proven to lower the levels of ammonia [ 22 , 36 , 37 , 38 ]. Thus, 11 Chinese herbal extracts were selected to validate their potential to minimize ammonia emissions from laying hens during in vitro fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicine extracts have the advantages of natural sources, no pollution, low cost, etc., and are rich in a variety of active substances and have a wide range of effects, which may have the potential to reduce ammonia gas in laying hens. Yucca extract has been proven to lower the levels of ammonia [ 22 , 36 , 37 , 38 ]. Thus, 11 Chinese herbal extracts were selected to validate their potential to minimize ammonia emissions from laying hens during in vitro fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, plant-derived products that contain secondary metabolites could help the animals to improve their health and production by reducing microbial resistance exhibited by pharmacological drugs (AZn) used in animal feed. Previously, Zúñiga-Serrano et al ( 27 ) reported that secondary plant metabolites are cost-effective for improving the production efficiency of non-ruminants. Feed costs play a determining factor in profitable and sustainable animal production.…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, the dietary addition of Yucca schidigera extract (YSE) was initially used to reduce stress and improve the antioxidant capacity of broilers, swine, dairy cows, and steers [ 2 , 3 , 4 , 5 , 6 ]. In addition to antioxidant function, the saponins in YSE also have antiprotozoal activity [ 7 ]. Saponin is a natural cholesterol binder that can produce a stable linkage to cholesterol on the surface of the cell membrane of a protozoan so that the integrity of the cell membrane is broken, resulting in cell lysis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%